Use of maropitant for the control of pruritus in non-flea, non-food-induced feline hypersensitivity dermatitis: an open-label, uncontrolled pilot study. Issue 10 (October 2019) - Maina, Elisa; Fontaine, Jacques
Objectives: Non-flea, non-food-induced hypersensitivity dermatitis (NFNFIHD) is a common inflammatory and pruritic skin disease in cats. When avoidance and conventional systemic immunosuppressive treatments fail to control the clinical signs, there are limited treatment options. The aim of this study was to evaluate the efficacy and tolerability of maropitant in feline NFNFIHD. Methods: In an open-label, uncontrolled study, cats with proven non-seasonal NFNFIHD were treated with maropitant 2 mg/kg PO q24h for 4 weeks. Clinical lesions were evaluated with the Scoring Feline Allergic Dermatitis (SCORFAD) system and pruritus was evaluated with a 10 cm visual analogue scale (VAS) before and at the end of the study. Owners assessed global efficacy and tolerability with a 4-point scale at the end of the study. Adverse events and body weight changes were recorded. Results: Twelve cats were treated with a mean initial maropitant dose of 2.22 mg/kg PO q24h. The treatment decreased both SCORFAD and pruritus VAS (pVAS) scores in all cats except one, in which only pruritus was reduced. The efficacy and the tolerability of the treatment were judged as excellent or good by 83.3% of owners. Treatment did not cause any side effects other than, in a few cases, short-time, self-limiting sialorrhoea. Conclusions and relevance: Maropitant seems to be an effective, well-tolerated therapeutic option to control pruritus in cats. Caution is needed in interpreting the results as the pVAS score system has not yet been validated in cats and the trial was uncontrolled. A further, controlled study is required to confirm our findings.